Migrant Learning Centers on the Thai-Myanmar Borderland: Giving New Meaning to "Live and Learn". Issue 3 (3rd May 2016) - Ball, Jessica; Dim, Angela
Abstract : "It is the weakest among us who need education the most and we cannot stand by as they are being excluded, " said Kishore Singh, UN Special Rapporteur on education, following the adoption of the Incheon Declaration at the World Education Forum in May 2015. He also called for "strategies to address inequality by focusing on girls and women, ethnic minorities, persons with disabilities and children living in conflict-affected areas, rural areas and urban slums." One especially vulnerable group that has been denied their right to education are the children caught up in forced migration along the Thai-Myanmar border. One strategy, highlighted in this article, for ensuring these children have access to quality early childhood education and complete primary education with effective learning outcomes, is nonformal, migrant alternative learning centers. The authors present a case study of one such center, New Blood School and Boarding House, to demonstrate the critical role alternative care systems can play in meeting the needs of marginalized children and ensuring that no child is left behind.